The Robin Heart robot 2010 – research report - Nawrat, Zbigniew (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
The presented work presents the current works led in Zabrze’s team connected with project of Robin Heart surgical robot. Two operations on pigs: cholecystectomia and the elements of repair operation of mitral and tricuspid valve were carried out in January 2009. TECAB – the operation the coronary by-pass on beating heart – have been passed to another date. It was decided to build a new robot. In May 2010 conducted the first experiment, a specially designed robot Robin Heart mc2. Purpose of the experiments has been achieved: new construction work has been accepted by the surgical team.